Comparative Study of Effect of Specific Yogasanas and Exercise in Obesity - Namrata B. Chouragade1 , Prashant S. Bhokardankar2 , Swapnil S. Bhirange3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The reason for the study is to analyze the impact of chosen Yoga-Pranayama on obese individual of influencedpeople, in Mahatma Gandhi Ayurvedic college Hospital and Research Centre, and Datta Meghe Institute ofMedical Sciences Wardha, Maharashtra. Sixty selected participants were arbitrarily separated in to twogroups of thirty each, out of which group I (N-30), underwent Yogasan and group II-aerobic exercise (N30). Pre-test and post test were directed for every one of the two groups on Weight, Basal Metabolic Index(BMI), chest circumference, abdominal circumference and waist circumference. The test group took part intheir separate chosen yogasana schedule for a time of about two months. In short the Post-test concentrateobviously demonstrates that there is a critical distinction of Weight, BMI, chest circumference, abdominalcircumference and waist circumference on pre-test and post test.